2019
DOI: 10.1371/journal.pone.0211142
|View full text |Cite
|
Sign up to set email alerts
|

Different operators and histologic techniques in the assessment of germinal center-like structures in primary Sjögren’s syndrome minor salivary glands

Abstract: ObjectiveA standardization of minor salivary gland (MSG) histopathology in primary Sjögren’s syndrome (pSS) has been recently proposed. Although there is strong agreement that germinal center (GC)-like structures should be routinely identified, due to their prognostic value, a consensus regarding the best protocol is still lacking. Aim of this study was to compare the performance of different histological techniques and operators to identify GC-like structures in pSS MSGs. MSG biopsies from 50 pSS patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
(44 reference statements)
0
9
0
1
Order By: Relevance
“…Detection of GCs in routine haematoxylin and eosin (H&E)‐stained sections can be challenging because small GCs may be overlooked and distinction between GCs and lymphoepithelial lesions may be difficult (Fisher et al, ; Haacke et al, ). Therefore, immunohistochemical identification using antibodies directed against CD21, expressed by FDCs (but also by B cells) or Bcl6, a transcription factor highly expressed by GC‐B cells, has been used (Bombardieri et al, ; Carubbi et al, ; Haacke et al, ), but consensus criteria regarding identification of GCs are lacking (Haacke et al, ). Hence, the aim of this study was to asses which staining is most suitable to unequivocally identify GCs in diagnostic salivary gland biopsies of pSS patients by comparing H&E, CD21 and Bcl6 stainings.…”
Section: Demographic Clinical and Histological Parameters Of Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of GCs in routine haematoxylin and eosin (H&E)‐stained sections can be challenging because small GCs may be overlooked and distinction between GCs and lymphoepithelial lesions may be difficult (Fisher et al, ; Haacke et al, ). Therefore, immunohistochemical identification using antibodies directed against CD21, expressed by FDCs (but also by B cells) or Bcl6, a transcription factor highly expressed by GC‐B cells, has been used (Bombardieri et al, ; Carubbi et al, ; Haacke et al, ), but consensus criteria regarding identification of GCs are lacking (Haacke et al, ). Hence, the aim of this study was to asses which staining is most suitable to unequivocally identify GCs in diagnostic salivary gland biopsies of pSS patients by comparing H&E, CD21 and Bcl6 stainings.…”
Section: Demographic Clinical and Histological Parameters Of Patientmentioning
confidence: 99%
“…In a recent study, Carubbi et al analysed the usage of CD3/CD20 as well as CD21 and Bcl6 as markers for the detection of GCs (Carubbi et al, ). While they conclude that combination of CD3/CD20 and CD21 should be recommended for assessment of GCs, we clearly show here that usage of CD21 as surrogate marker for GCs significantly overestimates GC counts.…”
Section: Demographic Clinical and Histological Parameters Of Patientmentioning
confidence: 99%
“…Regarding the histopathology of pSS, some conflicting data on the association between GC-like structures and lymphoma development can be explained by the lack of agreement on the methodology of assessment. 181 On the contrary, the association between higher FS and a higher risk of non-Hodgkin lymphoma was documented in several studies, and more recently, a FS ⩾4 was indicated as a risk factor for lymphoma development. 182 , 183 …”
Section: Lymphoma In Pssmentioning
confidence: 99%
“…The evolution into B-cell lymphoma represents one of the main causes of decreased survival in pSS and occurs in about 5% of patients (4). B cells play a major role in the pathogenesis of pSS via antibody-dependent and -independent mechanisms, and their hyperactivity, along with salivary gland infiltration and development of B-cell follicles containing germinal center-like structures, represents the hallmarks of the disease (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…B cells play a major role in the pathogenesis of pSS via antibody-dependent and -independent mechanisms, and their hyperactivity, along with salivary gland infiltration and development of B-cell follicles containing germinal center–like structures, represents the hallmarks of the disease ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%